Respuesta :
d + e = 15 ..... (i)
-d + e = -5 ........(ii)
From equation (i)
d + e = 15
e = 15 - d .......(iii)
Substitute (iii) into (ii)
-d + e = -5 ........(ii)
-d + 15 - d = -5
-d - d + 15 = -5
-2d = -5 -15 -2d = -20. Divide both sides by -2
-2d / -2 = -20 / -2
d = 10
From (iii) e = 15 - d
e = 15 - 10 = 5.
(d , e ) = (10 , 5).
Fourth option is the answer.
-d + e = -5 ........(ii)
From equation (i)
d + e = 15
e = 15 - d .......(iii)
Substitute (iii) into (ii)
-d + e = -5 ........(ii)
-d + 15 - d = -5
-d - d + 15 = -5
-2d = -5 -15 -2d = -20. Divide both sides by -2
-2d / -2 = -20 / -2
d = 10
From (iii) e = 15 - d
e = 15 - 10 = 5.
(d , e ) = (10 , 5).
Fourth option is the answer.
d + e = 15
-d + e = -5
If we add both equations, we get:
d + (-d) + e + e = 15 + (-5)
2e = 10
e = 5
There is only one answer choice that has e =5, and that is (10,5).
Just to be sure, let's solve for d.
d + e = 15
d + 5 = 15
d = 10
Your answer is D. (10,5).
-d + e = -5
If we add both equations, we get:
d + (-d) + e + e = 15 + (-5)
2e = 10
e = 5
There is only one answer choice that has e =5, and that is (10,5).
Just to be sure, let's solve for d.
d + e = 15
d + 5 = 15
d = 10
Your answer is D. (10,5).